2021
DOI: 10.1002/ardp.202000486
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, in silico, and in vitro studies of novel dopamine D2 and D3 receptor ligands

Abstract: Dopamine is an important neurotransmitter in the human brain and its altered concentrations can lead to various neurological diseases. We studied the binding of novel compounds at the dopamine D 2 (D 2 R) and D 3 (D 3 R) receptor subtypes, which belong to the D 2 -like receptor family. The synthesis, in silico, and in vitro characterization of 10 dopamine receptor ligands were performed. Novel ligands were docked into the D 2 R and D 3 R crystal structures to examine the precise binding mode. A quantum mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 86 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…The most common linkage between the primary and secondary pharmacophores was mediated via an aliphatic linker that is terminated by an ether 585,588,602,605,616,617,620,656,701,763,768,788 or a secondary amide 473,479,489,515,516,583,602,700,776,785,788,799 bond. The aliphatic ether was further modified by adding a double bond, 788 a triple bond, an aromatic, cyclohexyl ring or a cyclopropyl rings, 584,800 or switched to a cyclic ether, 483,793,801 thio‐ether, 488,670,672 an aliphatic linker without any heteroatom 599,600,670,672,802 or an aromatic amine 478 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common linkage between the primary and secondary pharmacophores was mediated via an aliphatic linker that is terminated by an ether 585,588,602,605,616,617,620,656,701,763,768,788 or a secondary amide 473,479,489,515,516,583,602,700,776,785,788,799 bond. The aliphatic ether was further modified by adding a double bond, 788 a triple bond, an aromatic, cyclohexyl ring or a cyclopropyl rings, 584,800 or switched to a cyclic ether, 483,793,801 thio‐ether, 488,670,672 an aliphatic linker without any heteroatom 599,600,670,672,802 or an aromatic amine 478 .…”
Section: Discussionmentioning
confidence: 99%
“…For the allosteric binding site, in addition to variously substituted benzamides 466–469,472,473,477,484,783,799 or 3,4‐dihydroquinolin2‐(1 H )‐one moiety, 800,804 also fragments such as 6,7,8,9‐tetrahydro‐4 H ‐pyrido[1,2‐ a ]pyrimidin‐4‐one, 805 xanthine core, 802 trazodone, 806 phthalimide, 482 imidazolidine‐2‐one, 807 talipexole 808 or 2‐aminomethylchromane 809 were used. Following the discovery of cariprazine containing urea group, various urea‐based derivatives such as aliphatic sulfonamides, amides, carbamates 527,590,594,595,700 or cyclic or aliphatic scaffolds were implicated as secondary pharmacophore 163,475,783 …”
Section: Discussionmentioning
confidence: 99%
“…The synthesis, in silico, and in vitro studies of novel SF5analogues of BP897, a potent D3R ligand (Ki =0.92nM), were reported by Stark at al. 55 (Figure 5). The synthesis of the target compounds was performed as shown in Scheme 62.…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…Scheme 62 Synthesis and affinity of dopamine D2 and D3 receptor SF5-ligands 55 The synthesis of a benzodiazepine Diazepam analogue bearing an SF5 group as a bioisosteric replacement of the chlorine atom was reported by Spencer et al 56 Acylation of commercially available 2-amino-5-SF5-benzophenone with chloroacetyl chloride followed by amination with hexamethylenetetramine, led to 7-SF5-5-phenyl-1H-benzo [1,4]diazepin-2(3H)-one, which was then converted into the desired compound by N-methylation (Scheme 63). Biological tests demonstrated that the substitution of Cl with the SF5 group led to a loss of potency (60-fold lower) in terms of potentiating GABAA receptor activation, probably due to a loss of ligand interaction with His102 in the GABAA receptor a subunit.…”
Section: Template For Synthesis Thiemementioning
confidence: 99%
See 1 more Smart Citation